THE RELATIONSHIP BETWEEN SCHOOL WELL-BEING AND ACADEMIC PROCRASTINATION ON STUDENT 10th GRADE of STATE MADRASAH ALIYAH - Annisa Annisa; Ika Febrian Kristiana (Jurnal EMPATI, 2014)
School is a part of learning environment that affect in forming student’s academic behavior including academic procrastination. Academic procrastination is delay either in initiating or completing academic assignments that lead to failure. Academic procrastination can be affected by school environment. The school environment is perceived differently by each student. The student’s perception of aspects having, loving, being, and health tend to be aspect that lead to the school satisfaction, also known as the school well-being. This research aimed to determine the relationship between school well-being and academic procrastination on student 10th grade of State Madrasah Aliyah. Population in this research was the student of State Madrasah Aliyah 1 and State Madrasah Aliyah 2 Banjarnegara. Cluster random sampling consisted of 224 students was used by researcher. This research used both the Academic Procrastination scale (rix = 0.92) and School Well-Being scale (rix = 0,84) that has been tested on 107 students. Product moment correlation revealed that correlation coefficient (rxy) of -0.477 which indicates that there is a negative relationship between well-being and the school academic procrastination. It indicates that the higher school well-being, the lower the academic procrastination and conversely, the lower the school well-being, the higher the academic procrastination.